Guide Conversation Method In English Speaking Learning For Business Administration Class - Cokorda Istri Mas Kusumaningrat (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
This study aims to determine the use of the guide conversation method in teaching speaking skillfor business at Business Administration Class of STISPOL Wira Bhakti Denpasar. This study uses a library research method, which is a research method based on expert opinions about speaking skills with the guide speaking method. So it can be concluded that learning English, especially speaking skills, requires a variety of precise strategies. The goal is to make it easier for students to learn English for business (English for special purposes) especially for telephoning, However, it should be remembered that learning English is not learning knowledge which requires high reasoning power, memorizing formulas, mastering tenses, grammar, and formal English grammar, and so on. However, learning English is nothing more than a skill that is continuously practiced until it is accustomed to it.